Parinaud syndrome: Any clinicoradiological correlation?. (26th June 2017) - Pollak, L.; Zehavi‐Dorin, T.; Eyal, A.; Milo, R.; Huna‐Baron, R.
Abstract : Introduction: The significance of MRI findings of patients with Parinaud syndrome (PS) with respect to clinical characteristics is poorly defined. Over the past decades, all patients with PS undergo magnetic resonance imaging which allows a better identification of the lesion localization. We compared the neuro‐ophthalmological findings of patients with PS caused by intrinsic (intra‐axial) vs extrinsic (pineal gland tumor) brainstem lesions. Methods: Medical records of patients with PS evaluated between 2000 and 2016 were retrospectively reviewed. Results: Twenty‐six patients with PS were included. Eight patients had pineal gland tumors and hydrocephalus. Two patients had hydrocephalus due to aqueduct stenosis and fourth ventricle tumor. Sixteen patients suffered from an intrinsic brainstem lesion and seven associated with hydrocephalus. The neuro‐ophthalmological findings did not differ between patients with extrinsic and intrinsic brainstem lesions. No correlation was found between the grade of hydrocephalus and number of clinical findings except for more findings in low‐grade hydrocephalus in intrinsic (40%) vs extrinsic (0%) lesions ( P =.003). Patients with moderate brainstem lesions and hydrocephalus had more clinical findings (65%) than patients with the same grade of brainstem involvement without hydrocephalus (29%) ( P =.03). The resolution rate of ophthalmological findings was comparable in all groups of patients. Conclusions: Our results did not show differences in neuro‐ophthalmological findings between intra‐ and extra‐axial lesions causing PS. However, the presence of hydrocephalus was an important factor influencing clinical findings. The prognosis of PS was less favorable than generally reported.